Building evaluation capacity of local substance abuse prevention programs serving LGBQ populations. (August 2017) - Valenti, Maria; Campetti, Randi; Schoenborn, Nicole; Quinlan, Kristen; Dash, Kim
Highlights: Few evidence-based substance use prevention programs exist for LGBQ populations. LGB organizations benefit from evaluation capacity building initiatives. Evaluators working with LGBQ programs face unique challenges. Evaluators should possess basic evaluation skills and LGBQ cultural competence.